High accuracy thermal resistance measurement in GaN/InGaN laser diodes. (April 2015) - Wen, Pengyan; Li, Deyao; Zhang, Shuming; Liu, Jianping; Zhang, Liqun; Zhou, Kun; Feng, Meixin; Li, Zengcheng; Tian, Aiqin; Yang, Hui
Highlights: A high accuracy thermal resistance measurement method is presented. Measurement time delay is shortened to 300 ns. The measured results are revised based on the simulation results. Real-time monitoring of the sensor current further improves the accuracy. The thermal resistance of TO56 packaged GaN/InGaN LD is 30.2 ± 0.3 K/W. Abstract: A thermal resistance measurement method of high accuracy for GaN/InGaN laser diodes (LDs) is presented based on the forward-voltage method. Three items are optimized in order to improve the accuracy of the measurement. (i) Measurement time delay is shortened to 300 ns by using the single trigger function of a MDO4104-3 Mixed Domain Oscilloscope. (ii) The measured results are revised based on the simulation result. (iii) The accuracy of the measurement is further improved by the real-time monitoring of the sensor current. Thermal resistance of the LD operating under different injection current is measured by using this method. The thermal resistance of TO56 packaged GaN/InGaN LD is 30.2 ± 0.3 K/W.